Kronično vnetje srednjega ušesa s holesteatomom - Četina, Marko (Zdravniški vestnik, 2008)
In the article an extensive recidivant cholesteatoma twelve years after primary operation in childhood with preservation of ear canal and reconstruction of ear bones ispresented. The case is interesting because in one patient three different complications are present (labyrinth fistula, destruction of facial nerve bony canal and skull base with dura exposure). There are also some data about surgery approaches, hearing results and discussion about complications.
Keywords: Adult; Audiometry, Pure-Tone; Avdiometrija, čisti-ton; Cholesteatoma, Middle Ear; diagnostika; hearing; Hearing Loss, Conductive; holesteatom; Holesteatom srednjega ušesa; kirurško zdravljenje; motnje; Odrasli; Otitis Media; Otitis, srednjega ušesa; Ponovitev; Recurrence; sluh; Sluh, izguba prevajalna; Surgery; uho; vnetja; zapleti